Active biomonitoring for assessing effects of metal polluted sediment resuspension on gammarid amphipods during fluvial traffic. (November 2016) - Prygiel, E.; Billon, G.; François, A.; Dumoulin, D.; Chaumot, A.; Geffard, O.; Criquet, J.; Prygiel, J.
Abstract: The resuspension of polluted sediments by boat traffic could release substantial amounts of metals to the water column, affecting at the same time their bioavailability. In order to characterize the impact of sediment resuspensions on biota, caged amphipods have been deployed on three different channelized watercourses in Northern France. Firstly, the biological responses of transplanted freshwater gammarid amphipods, Gammarus fossarum, described by trace metal accumulation, feeding and reproduction activities were quite similar for the three water courses despite the differences of metal contamination and navigability. Secondly, the concentrations of metals accumulated in gammarids never exceeded the contamination thresholds previously defined for Co, Cu, Cr and Zn. Values were in the same order of magnitude whatever the studied site despite: (i) large differences noticed in the sediment quality and (ii) some concentrations in the overlying waters exceeding the Environmental Quality Standards (EQS) defined by the Water Framework Directive. Conversely, Pb was highly bioaccumulated with values systematically exceeding the threshold value whatever the site. Therefore, the impact of navigation cannot be proved and the difference between the 3 monitoring periods is rather attributed to environmental variability, probably linked to the seasonality. Moreover, this study also confirms that organisms sampled from a local population in the vicinity of the three studied watercourses could be used as test organisms, leading to similar results than the ones obtained with reference gammarids initially used for developing all the biological responses. This would simplify and then promote the development of studies based on gammarid amphipod, G. fossarum, as bioindicators. Graphical abstract: Highlights: Boat traffic in navigated rivers contribute to resuspend contaminated sediments. Caged amphipods Gammarus fossarum were used to assess the resuspensions impacts. No increase of metal bioavailability nor toxicity were induced by boat traffic. Results were more linked to temporal variations than to navigation activities.